The Relationship between Music and Second Languages. La relación entre música y segunda lengua - Dalia Bartoli; M.ª Elena Gómez-Parra; Cristina A. Huertas-Abril (Universidad de Las Palmas de Gran Canaria, 2022)
This study stems from a research and teaching innovation project entitled iPlay School of Music and Languages, in collaboration with the HUM-1006 Research Group, Trinity College Spain-Portugal, and the Territorial Delegation of Education, Sport, Equality and Social Policies of Cordoba, which provides for the teaching of theoretical and instrumental music classes in English. The aim of this study is to find out whether exists a relationship between music learning and second languages learning by means of a questionnaire distributed among 32 students aged between 7 and 9 years old on the participants' taste for these two disciplines, their practice and study habits and their skills and abilities in both areas. The results confirm the existence of such a relationship and our conclusions indicate that further research is desirable to discover how the two processes can benefit from each other, with the aim of enhancing both music and second language learning.